2020
DOI: 10.3390/jmse8100752
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Overtopping Waves on Sea Dikes with Gentle and Shallow Foreshores

Abstract: Due to ongoing climate change, overtopping risk is increasing. In order to have effective countermeasures, it is useful to understand overtopping processes in details. In this study overtopping flow on a dike with gentle and shallow foreshores are investigated using a non-hydrostatic wave-flow model, SWASH (an acronym of Simulating WAves till SHore). The SWASH model in 2DV (i.e., flume like configuration) is first validated using the data of long crested wave cases with second order wave generation in the phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…A possible cause for this change in behaviour is that thin layered flows with a water depth on the promenade were not captured by DSPH because the water depth was smaller than a couple of particles high. The fact that SW1L/SW8L was also able to achieve a Very Good model performance for the overtopped flow layer thickness on the promenade (Table 3) indicates that a very good wave overtopping accuracy has been demonstrated as well, which is a confirmation of previous validation works on wave overtopping over a dike with a shallow foreshore modelled with SWASH [27,28].…”
Section: Bore Interactions On the Promenade And Impacts On The Vertical Wallsupporting
confidence: 80%
See 1 more Smart Citation
“…A possible cause for this change in behaviour is that thin layered flows with a water depth on the promenade were not captured by DSPH because the water depth was smaller than a couple of particles high. The fact that SW1L/SW8L was also able to achieve a Very Good model performance for the overtopped flow layer thickness on the promenade (Table 3) indicates that a very good wave overtopping accuracy has been demonstrated as well, which is a confirmation of previous validation works on wave overtopping over a dike with a shallow foreshore modelled with SWASH [27,28].…”
Section: Bore Interactions On the Promenade And Impacts On The Vertical Wallsupporting
confidence: 80%
“…Another example is SWASH, a non-hydrostatic NLSW equations model, where frequency dispersion is resolved by approximation of the vertical gradient of the non-hydrostatic pressure together with a vertical terrain-following grid in a multi-layer approach [24]. It has been shown to be a very efficient and accurate method for the simulation of wave transformations over a (barred) beach [25], including transfer of wave energy to the LWs [26], and mean overtopping discharge [27] and maximum individual overtopping volume [28] over dikes with a very shallow foreshore. However, SWASH has never been validated before for (overtopped) bore impact loading on vertical walls.…”
Section: Introductionmentioning
confidence: 99%
“…This process, known as wave overtopping, can result in damage to critical infrastructure and even loss of life. Despite recent studies which suggest that the flow properties of individual overtopping events are equally important (Altomare et al 2020a;Sandoval and Bruce 2018;Suzuki et al 2020), coastal structures worldwide are typically designed to resist a mean overtopping discharge per meter width of structure, q (m 3 /s or l/s per m)-which is often estimated using empirical formulas.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the overtopping flow velocity and layer thickness are used as input in some erosion models (Dean et al, 2010;Hoffmans, 2012;Van Bergeijk et al, 2021) to estimate the cover erosion and stability of earthen dikes. Pedestrian safety during wave overtopping was also assessed using the flow velocity and layer thickness (Endoh and Takahashi, 1995;Bae et al, 2016;Mares-Nasarre et al, 2019;Suzuki et al, 2020). Therefore, flow parameters including the flow velocity and layer thickness are also important for the design and reliability assessment of coastal structures.…”
Section: Overtopping Flow Parametersmentioning
confidence: 99%
“…The flow characteristics are key parameters to assess the pedestrian safety when standing on the coastal structures during the overtopping events (Mares-Nasarre et al, 2019). Suzuki et al (2020) suggested that the overtopping risk was better characterised by time dependent flow velocity and layer thickness than maximum flow parameters. Sandoval and Bruce (2018) provided different criterion for human stability on coastal structures.…”
Section: Practical Implications and Applicability For Hwbp Dmentioning
confidence: 99%